Private-Sector Development in Fragile, Conflict-Affected, and Violent Countries - Hameed, Sadika; Mixon, Kathryn (Rowman & Littlefield Publishers, 2013)
The CSIS Working Group on Private-Sector Development in Fragile, Conflict-Affected, and Violent States identifies tools available to the international business community and the U.S. government to assist these countries, as well as the gaps in needed resources. Participants examined cases from Afghanistan, Iraq, Burma, and Liberia to glean examples of successes and failures in private-sector development, with the goal of identifying potential roles for host governments and the international private sector. This report presents the results of those discussions.